The European Parliament’s Legislative Requests - Ridley, Stephanie (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2021)
This paper assesses the influence of the European Parliament on the legislative programme of the European Union. It discusses the European Parliament’s legitimacy as legislator, considers the nature of the European Parliament’s role within the European Union’s institutional framework, in particular its relationship with the European Commission, assesses whether recent developments have enhanced the European Parliament’s role and evaluates proposals for further reform. The mechanisms by which the European Parliament influences European Union legislation are outlined, with a focus on the European Parliament’s ability to steer the Commission’s legislative proposals, in particular by means of legislative requests under Article 225 of the Treaty on the Functioning of the European Union. A case study illustrates how such legislative requests work in practice.